Relative Age Effect (RAE) According to Norm Values on Anthropometric Performance and Physical Fitness in 9–11-Year-Old Children - Kryeziu Artan; Begu Bujar; Badau Dana; Iseni Astrit (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: The main purpose of this study is to identify the relative effect of age (RAE) according to norm values on the anthropometric performance and physical fitness of children between the ages of 9 and 11 years. The data, namely the percentiles of anthropometric parameters and physical fitness, are relevant for identifying the RAE in relation to gender and the month of birth in children. Methods: For the sample in this study, 1185 young people from Kosovo were enrolled, including 626 males and 559 females aged 9–11 years. The gathered data were assessed via the EUROFIT methodology, which takes into account comparisons based on the quartile of birth and the relative age effect (RAE). Results: The results of the data show us that there are significant differences in the RAE among children born in Q2 at the age of 9 years, especially in boys, as well as significant differences in the height variable at the <0.005 significance level. Others factors did not show significant differences, for example, variables that are indicators of physical fitness. For both boys and girls born in Q1, significant differences were mainly found in the indicators of explosive strength, flexibility, static strength, speed, and agility, with a level of significance of p < 0.001, while other indicators did not show significant differences. In addition, there was a significant difference the ratio between genders at the p < 0.001 and p < 0.005 levels, mainly among those born in Q1 and Q2. Similarly, at 10 years of age, children who were born earlier in the year had better scores, although the large disparities were more noticeable between quartiles than between genders, where the significant differences were mainly in the indicators of explosive strength, speed, and strength at the p < 0.001 level, as well as static strength, agility, and speed at the p < 0.005 level. Significant differences were also found for the indicators in terms of gender. At the age of 11, significant percentiles were mainly found in the quartiles at the beginning of the year for both boys and girls, and significant differences were also found at the p < 0.001 level for RAE between quartiles and gender. Conclusions: By using these data, it will be possible to highlight how males, who have demonstrated notable advantages in anthropometric and physical fitness measures, as well as those born in the first few months of the year, exhibit a relative age effect (RAE) in accordance with gender norm values.
Keywords: physical fitness; birth in RAE; chronological age; percentile values